การพัฒนาส่วนประสมการตลาดของผู้ให้บริการด้านการแพทย์ของไทยเพื่อรองรับตลาดอาเซียน - สุขเจริญ วุฒิ (วารสารปัญญาภิวัฒน์, 2013)
บทคัดย่อ การวิจัยในครั้งนี้มีวัตถุประสงค์ ได้แก่ 1) เพื่อศึกษาระดับความต้องการด้านส่วนประสมการตลาดในการไปรับบริการด้านการแพทย์ในต่างประเทศของประชากรในกลุ่มประเทศอาเซียน 2) เพื่อศึกษาความคิดเห็นของประชากรในกลุ่มประเทศอาเซียนต่อส่วนประสมการตลาดของผู้ให้บริการด้านการแพทย์ของไทย 3) เพื่อศึกษาแนวทางการพัฒนาส่วนประสมการตลาดของผู้ให้บริการด้านการแพทย์ของไทยสำหรับตลาดอาเซียน การวิจัยครั้งนี้เป็นการวิจัยเชิงปริมาณ เก็บข้อมูลจากประชากรในกลุ่มประเทศอาเซียนจำนวน 180 ตัวอย่าง ผลการวิจัยพบว่า ประชากรในกลุ่มประเทศอาเซียนมีความต้องการด้านบริการอยู่ในระดับสูงถึงสูงมาก ความต้องการด้านความเหมาะสมของราคาอยู่ในระดับสูง ความต้องการด้านสถานที่อยู่ในระดับปานกลาง ความต้องการด้านสื่อสารอยู่ในระดับสูง ผลการสำรวจความคิดเห็นต่อระดับส่วนประสมการตลาดของผู้ให้บริการด้านการแพทย์ของไทย พบว่า ด้านบริการอยู่ในระดับสูง ด้านราคาอยู่ในระดับปานกลางถึงต่ำ ด้านสถานที่อยู่ในระดับปานกลางถึงสูง และด้านการสื่อสารอยู่ในระดับสูง จากผลการศึกษาแนวทางการพัฒนาส่วนประสมการตลาดของผู้ให้บริการด้านการแพทย์ของไทยสำหรับตลาดอาเซียนโดยใช้สถิติ Paired sample t-test ที่ระดับนัยสำคัญ เท่ากับ 0.05 พบว่า ผู้ให้บริการด้านการแพทย์ของไทยควรปรับปรุง 5 ด้าน ได้แก่ 1) ความสามารถของแพทย์ ได้แก่ มุ่งเน้นการนำเสนอความสำเร็จของแพทย์ในด้านการให้บริการทางการแพทย์ในโรคที่ซับซ้อน 2) ความทันสมัยของเทคโนโลยี ได้แก่ มุ่งเน้นการนำเสนอผลการให้บริการทางการแพทย์จากการใช้เทคโนโลยีที่ทันสมัย 3) การบริการอื่นๆ ได้แก่ การเพิ่มบริการพิเศษ 4) ความเหมาะสมของค่าใช้จ่ายด้านการแพทย์ ได้แก่ การหาวิธีการลดค่าใช้จ่ายด้านการแพทย์ และ 5) ความเหมาะสมของค่าครองชีพ ได้แก่ การหาวิธีการลดค่าใช้จ่ายอื่นๆ คำสำคัญ: ส่วนประสมการตลาด ผู้ให้บริการด้านการแพทย์ ตลาดอาเซียน Abstract This research has three objectives which are 1) to study the level of demands of the ASEAN population on the marketing mix of receiving medical services abroad 2) to study the opinions of the ASEAN population on the marketing mix of the Thai medical service providers 3) to study the potential improvement on the marketing mix of Thai medical service provider for serving the ASEAN market. This research is quantitative research, collecting data from a sample of 180 members of the ASEAN population. The findings indicated that the ASEAN population had demands for service at the high to very high level, demands for suitable price at the high level, demands for place at the moderate level, and demands for communications at the high level. From the survey results on the marketing mix of the Thai medical service providers, it was found that service was at the high level, price was at the moderate to low level, place is at the moderate to high level, and communications was at the high level. From the study of potential improvement of the marketing mix of Thai medical service provider for serving the ASEAN market by using paired sample t-test significance level at 0.05, it was found that Thai medical service providers should improve 5 areas. These included 1) the ability of the physician, by focusing on the results of medical services such as the success of physicians in complicated medical procedures 2) the healthcare technology, by focusing on the results of using advanced technology in medical procedures 3) other services, by providing other special services 4) suitable medical expenses, by seeking a way to reduce costs of medical services and 5) suitable living costs, by seeking a way to reduce other expenses. Keywords: Marketing Mix, medical service providers, ASEAN market